Comprehensive genetic rescreening improves diagnostic yield in congenital hyperinsulinism - Männistö, Jonna M. E.; Houghton, Jayne A. L.; Bennett, Jasmin J.; Keskinen, Päivi; Tuomi, Tiinamaija; Ruuskanen, Heli; Viikari, Liisa A.; Jokiniitty, Antti; Lähde, Jyrki; Raivo, Joose; Otonkoski, Timo; Huopio, Hanna; et al. (Oxford University Press, 2026)
Context
Recent genetic discoveries in congenital hyperinsulinism (HI) and advances in sequencing technology suggest that the diagnostic yield may be improved by rescreening in people with genetically unsolved HI.
Objective
To evaluate this hypothesis in a nationwide cohort of individuals with a historical diagnosis of HI of unknown genetic cause.
Methods
Twenty-seven probands, representing 77% of the genetically unsolved HI cases in Finland, underwent rescreening which targeted the coding regions of 18 known HI genes, and 5 relevant non-coding regions. The median age of the cohort was 21 years (range, 4-44 years). Participants had previously undergone a median of 3 genetic tests (range, 1-4), all of which yielded negative (n = 17) or inconclusive (n = 10) results.
Results
Genetic rescreening was informative in 22% (6 of 27) of cases. Definitive genetic diagnoses were established in 4 (15%) participants. These included the detection of non-coding variants in the ABCC8, HK1, and SLC16A1 genes, and a GCK mosaic variant (8% allele fraction). In 2 (7%) cases, rescreening revised genetic results but did not provide a definitive genetic diagnosis.
Conclusion
In this Finnish cohort, rescreening with a comprehensive gene panel provided new or revised diagnoses in 22% of cases, informing on medical management and recurrence risk. These findings emphasize the importance of regularly updating genetic testing strategies and highlight the clinical value of re-evaluating the need for rescreening in genetically unexplained HI cases even following clinical remission.